The Mussel Shell Powder as Natural Preservation for Swordfish by Using Smearing Method - Demes Nurmayanti; Darjati Darjati; Marlik Marlik (Humanistic Network for Science and Technology (HNST), 2018)
Processing fish in order to be more lasting and be able to be still consumed by the people was needed good preservation. Fish could be lasting if the bacterial decomposition in the fish could be prevented. All this time, the people only used the waste of mussel shells for animal feed. Moreover, the mussel shells were not only used as animal feed, but also as additional material for concrete compound and natural preservation. Therefore, this research aimed at analyzing the use of mussel shells as natural preservation for swordfish. This research was experimental research with static group comparison design that aimed at knowing the use of mussel shell powder as natural preservation for swordfish. Organoleptic test conducted to the fresh fish, which included eyes, gill, mucus, meat, and smell. Time interaction and the concentration of mussel shell powder which was smeared on the swordfish gave significant influenced toward the number of total germ rate with determination coefficient (R2) was 99.8%. Besides, there was a difference of preservation of swordfish among 3:1 was the fish could be preserved until in 24 hours and the fish was able to be consumed and still in fresh condition with organoleptic value in average of 7.00, meanwhile, the fishes which were in the comparison between 1:1 and 2:1 were in rather spoiled condition. Furthermore, there was no significant difference of germ rate in swordfish after being smeared by mussel shell powder among 1:1, 2:1, and 3:1 in 12 hours, 24 hours,and 30 hours, in which the germ rate qualified the qualification. However, there was a significant difference when it was in 36 hours but the germ rate still did not qualify the qualification. Keywords: Swordfish, Mussel shell, Germ rate